Development and Performance Evaluation of a Micro-Scale RDF Briquette–Fueled Steam Power Prototype - Syarifah; Latricia Aina Hidayat; Rini Yunita Sari; Jerry Maratis; Andri Krisna Hidayat; Pawenary; Hendri (Advance Sustainable Science Engineering and Technology, 2026)
Plastic waste is a major environmental problem in Indonesia due to its non-biodegradable nature. One innovative solution is converting waste into energy using Refuse-Derived Fuel (RDF) briquettes for small-scale power generation. This research designed and tested an RDF-based micro power plant prototype using briquettes composed of 80% dry organic biomass and 20% plastic for safe and stable combustion. The prototype consists of a combustion chamber, heat exchanger, impulse-type micro steam turbine driven by low-pressure steam, and a 12V low-speed DC generator. Performance was evaluated through temperature, voltage, current, power output, and efficiency measurements. The highest performance was achieved using 500 g of RDF, producing 0.02 A, 0.7 V, and 0.014 W at 135°C over 20 minutes, with an efficiency of 2.69×10⁻⁶%. Although efficiency was very low, the study demonstrates proof-of-concept feasibility and provides a baseline for future optimization of thermal and energy conversion efficiency.